O acompanhamento em um serviço de saúde auditiva: indicadores de habilidades auditivas e de linguagem em crianças menores de três anos - Ribeiro, Bruna Marcondes (2008)
Introduction: The importance of early diagnosis and amplification is directly related to immediate intervention. Indicators of language and auditory development of hearing impaired children are the basis for the follow up and referral procedures involved in the regular visits to the High complexity service responsible for the child. Goal: To describe and discuss indicators of language and auditory development in children younger than three years old, through a longitudinal study in a high complexity service within the Hearing Health System. Specifically, it aims at analyze different aspects of language and auditory development with the inclusion of additional instruments, such as, therapy data and parental involvement rating, and the implications for clinical decisions within the follow up visit, as stated in the Portaria MS/SAS Nº 587, October 07, 2004. Method: Descriptive, longitudinal study of three cases of hearing impaired children diagnosed early as well as their parents, all enrolled in early intervention program. IT MAIS, MUSS and MacAthur (CDI), Interview guide for parents, Family involvement rating scale, clinical records, research diary were used in data collection. Results: Using the CDI we observed that, in terms of vocabulary, children understand more than they produce, and demonstrated vocabulary increments in the longitudinal perspective, even though below parameters established for their ages. In two of the subjects IT MAIS rapidly reached maximum scores, demonstrating that it is not effective for moderate hearing losses. Data obtained through the family involvement rating scale and the interview guide enabled the observation f significant differences among the families. The research diary also offered unique information about the development of each child. Conclusions: The IT MAIS scale was not sensitive for the subjects with moderate loss. MUSS brought limited information about oral language skills, which were limited to the initial stages. It was suggested that additional instruments are necessary. CDI was sensible to intra-subject vocabulary growth; however its length was very annoying to the parents. The instruments related to parental involvement allowed for rating of family participation and expectations towards their children. It was suggested that, during the follow up visit to the High complexity service, a written protocol, filled out by the therapist should be included. Information including general development and behavior as well as family involvement can add important information that will contribute to the case management in the follow up visit within the Hearing Health System